Macro-Seismic Assessment for Residential Buildings Constructed in the Soviet Union Era in Almaty, Kazakhstan - Muhammad Sajjad Rashid; Dichuan Zhang; Sung-Woo Moon; Dana Sarkulova; Yeraly Shokbarov; Jong Kim (Buildings, 2023)
Southern and southeastern Kazakhstan is a region of intraplate seismicity characterized by several destructive earthquakes. Almaty, the largest metropolis in this region, has many structures with different construction materials and seismic-resistant systems. Among them, residential buildings constructed in the Soviet Union era (before the 1990s) may possess low seismic resisting capacities due to limited seismic design and detailing provisions. Therefore, it is essential to assess seismic risks for these buildings. This paper collected information from a government agency (i.e., KazNIISA), including construction materials, lateral force-resisting systems, and structural ductility capacities for residential buildings constructed in this era. These buildings were then categorized in terms of their seismic vulnerabilities following the European Macro-seismic Scale (EMS-98). Vulnerability curves and probability of damages were developed under different earthquake intensities and peak ground accelerations. The likelihood of varying levels of damage was established for the design basis and maximum considered earthquakes in the Almaty region. It was found that unreinforced masonry and wood buildings tend to be very heavily damaged and even collapse under the maximum considered earthquake. The reinforced and precast concrete buildings have a high probability of heavy to very heavy damage, which may require further analytical assessment since the structure at this damage level will undergo a significant nonlinear response and has a high uncertainty in the seismic performance.